3x+5=7x-23

Simple and best practice solution for 3x+5=7x-23 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x+5=7x-23 equation:


Simplifying
3x + 5 = 7x + -23

Reorder the terms:
5 + 3x = 7x + -23

Reorder the terms:
5 + 3x = -23 + 7x

Solving
5 + 3x = -23 + 7x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-7x' to each side of the equation.
5 + 3x + -7x = -23 + 7x + -7x

Combine like terms: 3x + -7x = -4x
5 + -4x = -23 + 7x + -7x

Combine like terms: 7x + -7x = 0
5 + -4x = -23 + 0
5 + -4x = -23

Add '-5' to each side of the equation.
5 + -5 + -4x = -23 + -5

Combine like terms: 5 + -5 = 0
0 + -4x = -23 + -5
-4x = -23 + -5

Combine like terms: -23 + -5 = -28
-4x = -28

Divide each side by '-4'.
x = 7

Simplifying
x = 7

See similar equations:

| 0.6(x+50)+0.4x=55 | | p^2+169=26p | | 12x^2-2x-21= | | 0.4(x+200)=0.45x-305 | | 4=-z+2 | | 2s+3s^2= | | (6w-8)(-6w^2+1w+9)= | | 8x+54=2x-102 | | 4x^2-16x-91=-7 | | 7+4x=-25 | | 17+p=-14 | | 2x-8=3x-102 | | 5x-11x+6=0 | | 7=0.5m | | 1x+56=-6x+119 | | 3p-6=3p-p | | 5e=4.5 | | -163=7x+6(-3x-18) | | X+4(1-x)=-17 | | 9-4y-12=-10y-25 | | 8+2p=2 | | 1234326567898780-098543=g-12345678756 | | 14k+5=k+14 | | 9x+11=4+5x+2x | | (3+-9x)+9x=3 | | -8=28-5x | | -20-15y=-17 | | 2(2x+3y)(3x-4y)= | | 10g-3x+10=8 | | 2x-8=3x-120 | | -15.5=2.5+3.5(d-7) | | -6-2x=32 |

Equations solver categories